Mentoring Activities for the Mathematics Olympiad Module in Elementary Schools - Alfiani Athma Putri Rosyadi; Ahsanul Inam; Arif Hidayatul Khusna (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Mathematics olympiad is one of the routine activities that is followed by the school level, especially elementary schools. One of the elementary schools that regularly takes part in the Olympics is SD Muhammadiyah 9 Malang. Based on the results of interviews with teachers, information was obtained that in SD Muhammadiyah 9 Malang, Olympic guidance activities were still not optimal. In addition, there are no modules specifically provided for Olympic activities. This is what makes the service team to accompany teachers at the elementary school to conduct Olympic guidance. Service preparation activities include socialization and delivery of information on activity plans. Furthermore, socialization and implementation of activities. Implementation of activities includes workshops and the preparation of mathematics olympiad modules. The output of this community service activity is the Mathematics Olympiad module and its application in guidance activities.